Semi-spherical Radiofrequency Bipolar Device - A New Technique for Liver Resection: Experimental In Vivo Study on the Porcine Model - Vavra, P; Penhaker, M; Jurcikova, J; Skrobankova, M; Crha, M; Ostruszka, P; Ihnát, Peter; Grepl, J; Delongova, P; Dvorackova, J; Prochazka, V; Salounova, D; et al. (Technology in cancer research & treatment, 2015)
The incidence of colorectal carcinoma is still growing in the Czech Republic and also all around the world. With success of oncological treatment is also growing a number of potential patients with liver metastases, who can profit from surgical therapy. The aim of this study was to confirm on porcine models that this method by using new surgical device is effective and safe for patients who have to undergo liver resection. The primary hypothesis of the study was to evaluate whether this new device is able to consistently produce homogeneous and predictable areas of coagulation necrosis without the Pringle maneuver of vascular inflow occlusion. The secondary hypothesis of the study was to compare the standard linear radiofrequency device and a new semi-spherical bipolar device for liver ablation and resection in a hepatic porcine model. Twelve pigs were randomly divided into two groups. Each pig underwent liver resection from both liver lobes in the marginal, thinner part of liver parenchyma. The pigs in first group were operated with standard using device and in the second group we used new developed semi-spherical device. We followed blood count in 0(th), 14(th) and 30(th) day from operation. 14(th) day from resection pigs underwent diagnostic laparoscopy to evaluate of their state, and 30(th) day after operation were all pigs euthanized and subjected to histopathological examination. Histopathological evaluation of thermal changes at the resection margin showed strong thermal alteration in both groups. Statistical analysis of collected dates did not prove any significant (p < 0.05) differences between standard using device and our new surgical tool. We proved safety of new designed semi-spherical surgical. This device can offer the possibility of shortening the ablation time and operating time, which is benefit for patients undergoing the liver resection.
Keywords: Animals; Czech Republic; Hepatectomy; hepatektomie; zvířata; Disease Models, Animal; Catheter Ablation; Colorectal Neoplasms; Female; nádory jater; Male; katetrizační ablace; Sus scrofa; laparoskopie; Česká republika; Liver Neoplasms; kolorektální nádory; ženské pohlaví; játra; modely nemocí na zvířatech; Laparoscopy; mužské pohlaví; Liver